A novel case tool based on pre-conceptual schemas for automatically obtaining uml diagrams (2007)
Assistance is provided, in software development process, to Analysts in drawing UML diagrams and others by means of CASE tools. However, the task of the Stakeholder discourse understanding, a previous process in diagram drawing, is not supported by traditional CASE tools. In order to complete this task, Natural Language Processing has proposed a new kind of CASE tools, including both natural language interpretation and UML diagrams generation. We introduce, in this paper, UNC–Diagrammer, a novel CASE tool for graphically representing the Stakeholder discourse by means of Preconceptual Schemas. We also show that UNC-Diagrammer is capable of automatically transforming Pre-conceptual Schemas into three UML 2.0 diagrams. We finally demonstrate the use of UNC–Diagrammer through an example.